Economics of the 1% how mainstream economics serves the rich, obscures reality and distorts policy - Weeks, John 1941- (Anthem Press, 2014)
How much do economists really know? In most cases, they claim to have profound knowledge but in fact understand little and obscure almost everything. Most people are convinced that economics should be left to the 'experts', when they themselves are perfectly capable of understanding it. This book explains that mainstream economics serves the interests of the rich through its logical inconsistency and unabashedly reactionary conclusions. John F. Weeks exposes the myths of mainstream economics and explains in straightforward language why current policies fail to serve the vast majority of people in the United States, Europe and elsewhere. Their failure to serve the interests of the many results from their devoted service to the few